The effect of uncertainty in composition on laser-induced grating thermometry - Edwards, M (2011)
The effect of uncertainty in gas composition on the accuracy of gas-phase thermometry using Laser-Induced Thermal Grating Spectroscopy, LITGS, is studied. Temperatures are obtained from measurements of the sound speed derived from the frequency of oscillations ƒOSC imposed upon the LITGS signal arising from the transit of acoustic waves across the density modulation feature. The dependence of the sound speed, cs on √γ/m, where γ is the ratio of specific heats and m is the mean molecular mass leads to a dependence upon gas composition. LITGS signals were generated in acetone vapour in a variety of gas mixtures in a temperature controlled cell at 4 bar total pressure using pump pulses from a frequency quadrupled Q-switched Nd:YAG laser at 266 nm and a cw diode pumped solid state probe laser at 671 nm. Studies were undertaken of the variation in ƒOSC with gas composition using gas mixtures of O2 and N2 with component concentrations in the range 0-100 %, and was found to agree with theoretical predictions. Measurement precision of the data (one standard deviation in 50 measurements) was found to be typically ± 1.7 % for measurements at 4 bar total pressure. The effect of varying concentrations in exhaust gas residuals (EGR) typical of pre-ignition gases in a spark ignition internal combustion engine were studied using synthetic air (N2/ O2 mixtures) containing variable amounts of simulated EGR components, CO2 and H2O. The effect of variation in CO2 concentration in dry synthetic air was measured at 4 bar and 30°C and found to agree with theoretical predictions. Experiments conducted at 30°C, with the addition of a saturated vapour pressure of water indicate that the effect of a saturated vapour pressure of water on the oscillation frequency in synthetic EGR is on the borderline of resolution. The effect of variable amounts of typical hydrocarbon fuel vapour on ƒOSC was studied using 2,2,4-trimethyl-pentane in gas mixtures composed of synthetic air and variable amounts of EGR and water vapour at 80°C. Kinetic theory was used in order to model the dependence of the oscillation frequency ƒOSC on various gas compositions containing fuel and EGR, in order to construct an error surface for comparison with experimental measurements. Experimental data were found to agree with the model predictions to within experimental error for a representative data set within the range of calculated values. The results indicate that uncertainties in temperature values derived from LITGS thermometry can be estimated with confidence within reasonable estimates of composition variations in an internal combustion engine, and should lead to absolute temperature accuracy of within 2-3 %.